2017
DOI: 10.1016/j.cmet.2017.05.015
|View full text |Cite|
|
Sign up to set email alerts
|

Microglial Inflammatory Signaling Orchestrates the Hypothalamic Immune Response to Dietary Excess and Mediates Obesity Susceptibility

Abstract: SUMMARY Dietary excess triggers accumulation of pro-inflammatory microglia in the mediobasal hypothalamus (MBH), but the components of this microgliosis and its metabolic consequences remain uncertain. Here, we show that microglial inflammatory signaling determines the immunologic response of the MBH to dietary excess and regulates hypothalamic control of energy homeostasis in mice. Either pharmacologically depleting microglia or selectively restraining microglial NF-κB-dependent signaling sharply reduced micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
317
2
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 360 publications
(345 citation statements)
references
References 58 publications
14
317
2
12
Order By: Relevance
“…; Valdearcos et al . , ; Dorfman and Thaler ). On the other hand, here it is found that in the male Sim1‐Cre:Rosa‐mEGFP mice exposed to the palm oil‐based HF diet, neuronal damage in the PVN is not paralleled by reactive microgliosis (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Valdearcos et al . , ; Dorfman and Thaler ). On the other hand, here it is found that in the male Sim1‐Cre:Rosa‐mEGFP mice exposed to the palm oil‐based HF diet, neuronal damage in the PVN is not paralleled by reactive microgliosis (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…; Valdearcos et al . , ; Dorfman and Thaler ). Moreover, in male rodents, exposure to HF diet induces impaired post‐translational processing of POMC to generate α‐MSH, loss of POMC neuron synapses, and impaired secretion of α‐MSH (Levin ; Enriori et al .…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, MBH gliosis might be an early finding in children that predisposes them to future insulin resistance indirectly via an effect favouring visceral fat deposition. In rodent models of diet‐induced obesity (DIO), inflammatory responses from glial cells, including astrocytes and microglia, have been shown to be necessary for the hyperphagia and weight gain seen during high fat feeding, but discerning if MBH gliosis is a marker or pathogenic component of obesity and insulin resistance in humans will require additional and longitudinal data, as the current cross‐sectional design limits such interpretations. In addition, dietary factors related to MBH gliosis in humans have yet to be defined and are important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dietary factors related to MBH gliosis in humans have yet to be defined and are important area for future research. Studies with rodent models have commonly implicated the HFD, but sucrose ingestion and neonatal overnutrition could also contribute to the inflammatory process and altered glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation